AN ANALYSIS OF WEBIZ USAGE IN KANSAS SCHOOLS - Poole, Heather (My University, 2019)
Kansas Department of Health and Environment (KDHE) is a state agency that is responsible for Kansas’ public health, environment, and health care finance. The Kindergarten Immunization Coverage Survey is an annual survey conducted by the Kansas Immunization Program (KIP) to determine vaccine coverage levels among children enrolled in a public or private school with a kindergarten class in Kansas. The Kansas immunization information system (IIS), WebIZ, serves as a database for Kansas immunization data. To validate the viability of WebIZ data at the population level, IIS data was examined for completeness and compared to current methodology used in the Kindergarten Vaccine Coverage Study. KDHE would like to use WebIZ as the data source for kindergarten immunization coverage, in efforts to reduce the cost and resources spent on the annual assessment. Part II of this study determined current usage of the WebIZ school module by schools in Kansas with a kindergarten class. Immunization data was pulled for all students assigned to a kindergarten class in a public or private school from WebIZ for the 2017-2018 academic year. An online survey was developed to assess the current usage and identify barriers to WebIZ utilization among schools to understand why such a large percentage of schools did not have associated kindergarten students in WebIZ. Barriers assessed included lack of time, lack of knowledge, lack of access, and use of another electronic immunization system or paper records. The greatest barrier associated with not using WebIZ was lack of access (OR=23.20). Lack of knowledge, use of an alternate electronic database, and use of paper records were also statistically significant barriers to WebIZ usage identified. Information from each of these studies will be used to guide future interventions to increase WebIZ utilization by schools in Kansas.
Keywords: immunization; IIS; vaccinations; school nurse